A Comprehensive Review of New Trends in the Use of Geosynthetics Clay Liner GCLs in Landfill - Kawther Y. H. AL-Soudany, Mohammed Y. Fattah, Falah H. Rahil (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Open dumping sites are what most dumps in developing countries often known as landfills are called because they lack a liner, a drainage layer, and adequate cover. If not managed effectively, landfills may contaminate surface water and groundwater via leachate intrusion into land and aquifers. The resulting leachate poses a serious threat to human health and the environment due to its constituents’ toxic and tenacious nature. Waste containment facilities are one of the geotechnical systems that use the most geosynthetic kinds for all purposes. There will likely be an uptick in the usage of geosynthetic components as companies innovate and produce better materials and engineers/designers create analytical algorithms for novel applications. In this study, we provide the key results, emphasizing the critical factors determining Geosynthetic Clay Liners (GCLs) service life. The design implications of using GCLs are also discussed, giving the reader a broad perspective.